Genes or Jeans? A Peircean Semiotic Analysis of Co-Occurrence and Dual Interpretation in the “Sydney Sweeney Has Great Jeans” Advertisement - Mila Amanda; Dedi Sulaeman; Myrna Nur Sakinah (Lingua Susastra, 2026)
This study examines how co-occurring sign-processes in an advertisement generate multiple interpretations. The object of analysis is the Sydney Sweeney Has Great Jeans advertisement released by American Eagle in July 2025. The advertisement attracted widespread public attention because it gave rise to two publicly documented interpretations: a commercial interpretation confirmed by the brand and a biological interpretation associated with eugenics discourse reported in news media. Drawing on Peirce's trichotomies and Bateman's account of co-occurring sign-processes, this study analyzes the verbal and visual elements across four selected segments using a descriptive qualitative approach. The findings show that the ambiguity does not result from the combination or blending of different sign categories into a single sign. Rather, it arises from the co-occurrence of distinct verbal and visual sign-processes in which the phonetic qualisign /dʒiːnz/ is realized as a spoken sinsign capable of instantiating two competing symbolic legisigns, “genes” and “jeans”. These sign-processes enable divergent dynamic interpretants to develop simultaneously.